DAMPAK KEPESERTAAN BPJS BAGI PEKERJA INFORMAL DI BOGOR - Fredi Andria; Nandang Kusnadi (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2017)
ABSTRACTHealth insurance available in Indonesia is still very limited in scope, given to a small proportion of the Population of Beneficiaries (PBI) and formal workers. This is also the case in the Bogor region, whereas the informal sector population in Bogor dominates more than 70%. The participation of the informal sector population in Bogor City is still low, reaching only 30% of the total population. Informal sector workers working in small firms, entrepreneurs in the informal and underemployed or elderly economic sectors, will rely on personal insurance or assistance from close and distant relatives and local communities, resulting in a very limited sustainability of group health insurance. In order to increase membership and coverage of health insurance can be expanded, the groups of informal sector workers in the area of Bogor must be recognizable and at the same time can be distinguished by their characteristics. It is necessary to define various segments of informal sector workers. More specifically, it is necessary to establish the mechanisms of the population engaged in the informal sector to be optimized for their participation in the health insurance program coordinated by the BPJS. Therefore it is necessary to analyze the needs of social health insurance system based on identification of informal workers (case study in Bogor city), so that the impact of health insurance (BPJS) partnership can be constructed for informal sector people.Keywords: BPJS, Health Insurance, Informal Sector, Partnership